PERBEDAAN HASIL BELAJAR MENGGUNAKAN METODE PROJECT BASED LEARNING DENGAN METODE KONVENSIONAL DALAM PEMBELAJARAN SENI RUPA SISWA KELAS X SMA NEGERI 2 KOTA SOLOK - SUSI RIANTINI, Dr. Yahya, M.Pd, Dr. Ramalais Hakim, M.Pd (Universitas Negeri Padang, 2015)
The purpose of this study was to know the differences of the learning result of the students by using project based learning and conventional learning in grade X of SMA N 2 Solok on Visual Art Education. This research applied used a quasi-experimental quantitative research which drafts Pretest-Posttest Control Group Design. The populations of this research were all students of class X SMAN 2 Solok. The samples of this research were class X2 as experimental (PjBL) and class X3 as control (conventional), the samples were taken by using random sampling techniques. Based on the hypothesis test conducted that the tvalue=18.369 and ttable=2.040. It means tvalue>ttable, then Ho is rejected and Ha is accepted, means that the average (mean) value of the experimental class and the control class are not identical or different. It can be concluded that there are the differences of the learning result of the students by using project based learning and conventional learning in grade X of SMA N 2 Solok on Visual Art Education.Keywords: Project Based Learning, Conventional Learning, Visual Art Education